HUBUNGAN ASUPAN ENERGI, MAKRO DAN MIKRONUTRIEN DENGAN TEKANAN DARAH PADA LANJUT USIA (Studi di Rumah Pelayanan Sosial Lanjut Usia Wening Wardoyo Ungaran, Tahun 2017) - Simamora, Deborah; Kartasurya, Martha Irene; Pradigdo, Siti Fatimah (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
High intake of saturated fat, sodium and low intake of calcium and magnesium can increase blood pressure. The prevalence of hypertension at Wening Wardoyo Elderly Social Service House, Ungaran was quite high (25.5% had systolic hypertension). The purpose of this research was to analyze the correlations between energy intake, macro, and micronutrients and blood pressure on elderly at Wening Wardoyo Elderly Social Service House, Ungaran. This study was an explanatory research with a cross-sectional design. Subjects in this study were 26 elderly men and women, aged 60-90 years old, who were chosen by purposive sampling technique. Systolic and diastolic blood pressure was measured by the researchers using a digital tensimeter. Data collection on food intake was conducted by Food Weighing, which then were processed by nutrisurvey. Data analysis was done using Pearson Product Moment correlation test. The results showed that 26.9% of respondents had systolic prehypertension, 19.2% of them were in the first phase, 23.1% had diastolic prehypertension, and 3.8% had diastolic hypertension at the first phase. Among respondents, 69.9% had moderate energy intake, 88.5% of respondents had excessive saturated fat intake, and 88.5% of respondents had lack intake of magnesium. All respondents had a low sodium intake, as well as a reduced intake of calcium. There was a correlation between saturated fat intake with systolic (r=0.758; p=0.003) and diastolic (r=0.856; p=0.001) blood pressures. There was no correlation between the energy adequacy level, sodium intake, calcium intake and magnesium intake with systolic and diastolic blood pressure. It recommended for the institution administrators to arrange the new menu by reducing high saturated fat foods.